Parkinson's Disease Is Not Simply a Prion Disorder - Surmeier, D. James (J Neurosci, 2017)
The notion that prion-like spreading of misfolded α-synuclein (α-SYN) causes Parkinson's disease (PD) has received a great deal of attention. Although attractive in its simplicity, the hypothesis is difficult to reconcile with postmortem analysis of human brains and connectome-mapping studies. An alternative hypothesis is that PD pathology is governed by regional or cell-autonomous factors. Although these factors provide an explanation for the pattern of neuronal loss in PD, they do not readily explain the apparently staged distribution of Lewy pathology in many PD brains, the feature of the disease that initially motivated the spreading hypothesis by Braak and colleagues. While each hypothesis alone has its shortcomings, a synthesis of the two can explain much of what we know about the etiopathology of PD. Dual Perspectives Companion Paper: Prying into the Prion Hypothesis for Parkinson's Disease, by Patrik Brundin and Ronald Melki